B cell-extrinsic and intrinsic factors linked to early immune repletion after anti-CD20 therapy in patients with multiple sclerosis of African ancestry - Silverman, Gregg J.; Amarnani, Abhimanyu N.; Arbini, Arnaldo A.; Kim, Angie; Kopinsky, Hannah; Fenyo, David; Kister, Ilya (Frontiers in Immunology, 2025)
IntroductionRecent investigations have identified patients of African ancestry (AA) with Multiple Sclerosis (MS), who display more rapid B-cell repopulation after standard semi-annual infusions with an anti-CD20 monoclonal antibody for B cell depletion. In this study, we explored the immunologic and genetic factors, with serum drug monitoring, that may contribute to a faster rate of B-cell repletion that follows during recovery from treatment with anti-CD20 antibody.MethodsIn AA MS patients treated with an anti-CD20 antibody that had early repopulation of peripheral blood B cells, we assessed for extrinsic factors, including the presence of anti-drug antibodies against ocrelizumab, which may contribute to early repletion. We also documented the associated serum drug levels. In addition, we examined for inheritance of intrinsic gene polymorphisms associated with B cell survival and immune function. ResultsOur findings identified a subset of AA patients with early B cell repletion after anti-CD20 treatment associated with anti-drug antibodies and an absence of detectable drug. Furthermore, a separate set of AA patients with the early B cell repletion phenotype without anti-drug antibodies had significant over-representation of genetic polymorphisms that map to genes for the B cell survival factor, BAFF, to antibody-dependent cytotoxicity, and to pathways involved in inflammation, leukocyte activation and B cell differentiation. DiscussionIn AA patients with MS, after anti-CD20 antibody treatment we found an unexpected high occurrence of early B cell replenishment. This was associated with the presence of anti-drug antibodies and/or specific genetic polymorphisms. Larger studies are now needed to determine whether these factors may lead to impaired therapeutic benefits of B cell targeted therapy and clinical progression, and these findings may be useful to guide future optimized personalized therapeutic strategies.